Virtual Mediation in the Field of Intellectual Property - Blashchuk, Tetiana; Shmyndruk, Olha; Buha, Volodymyr; Pysmenna, Olena; Popova, Natalia (Cuestiones Políticas, 2020)
The work aims to analyze the theoretical aspects of the use of information technologies in the mediation process, as well as the aspects of its implementation. The purpose of the investigation is online mediation as a form of resolution of intellectual property disputes. In addition, the topic of study is the social relationships that arise when using information technologies and mediation to resolve civil conflicts in the field of intellectual property. The research methods used in this case are the dialectical method, the generalization method, the comparison method, the analysis method, the synthesis method, the method in administration and the deduction method, the modeling method, and the abstraction method. As a result of the study, conclusions are drawn on the state of online mediation in the real world, the benefits and potential problems of introducing virtual mediation for disputed parties, the need for support for special applications, along with the need for the introduction of online mediation at the state level to a state policy.